"A Run-in with the Cops Is Really Few and Far Between": Negative Evidence and Ethnographic Understanding of Racial Discrimination by Police. Issue 1 (2nd January 2017) - Jacques, Scott
ABSTRACT: Statistics show that blacks are subjected to disproportionately more policing than whites, and more often interpret their encounters with police as affected by racial discrimination. The ethnographic evidence supports the numbers, but this body of work, I suggest, has been too focused on blacks' experiences with prejudicial policing. A fruitful but largely unexplored way to advance the ethnographic study of police discrimination is to collect and analyze data from the group receiving preferential treatment from officers: whites. In practice, this often involves collecting and analyzing nonevents, such as not being stopped by police. This article's purpose is to outline and illustrate the benefits and difficulties of such research by drawing on Lewis and Lewis's 1980 typology of "negative evidence" and findings from my study of 30 white drug dealers.